(untitled) (Global Journal of Science Frontier Research, 2017)
This paper recapitulates the role of legume forage meal supplementation on feed intake, weight gain, and digestibility and carcass characteristics of ruminant livestock. The different research works that had been carried out on ruminant livestock that fed on a basal diet of roughage based diets and supplemented with leaf meal(hay) of forage legumes demonstrated that supplementation of legume forages stimulated microorganism function in the rumen, reduced retention time and thus increased the intake of the feeds. Furthermore, different research output demonstrated the advantages of forage legume supplementation in process of digestibility which had depicted that supplementation of legume forages such as Lablab purpureus, Cowpea, pigeon pea, alfalfa and Sesbania sesba, Tagasaste, L. pallida, Desmodium leaf meal (hay) had played significant role in improvements in digestibility of DM, OM, CP, NDF and ADF.